2019
DOI: 10.3390/ijms21010253
|View full text |Cite
|
Sign up to set email alerts
|

Citrus Auraptene Induces Glial Cell Line-Derived Neurotrophic Factor in C6 Cells

Abstract: We previously demonstrated that auraptene (AUR), a natural coumarin derived from citrus plants, exerts anti-inflammatory effects in the brain, resulting in neuroprotection in some mouse models of brain disorders. The present study showed that treatment with AUR significantly increased the release of glial cell line-derived neurotrophic factor (GDNF), in a dose- and time-dependent manner, by rat C6 glioma cells, which release was associated with increased expression of GDNF mRNA. These results suggest that AUR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…A number of recent studies showed that glial cells might be a cellular target for therapeutic approaches to treat several neurodegenerative diseases and neurological disorders, because glial cells, especially astrocytes, serve as key elements in the formation, maintenance, and refinement of synapses [13][14][15]. In our earlier studies regarding the neuroprotective ability of AUR, we revealed that (1) AUR has the ability to suppress inflammatory responses in vivo, namely, hyperactivation of microglia/astrocytes, and over-expression of inflammatory factors by astrocytes, in some mouse models of brain disorders; thus, resulting in the suppression of neuronal death in the hippocampus [3][4][5][6]; and (2) AUR has the ability to induce GDNF expression in C6 cells [9] in vitro. This series of our studies thus suggested that the site of neuroprotective ability of AUR might be astrocytes.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…A number of recent studies showed that glial cells might be a cellular target for therapeutic approaches to treat several neurodegenerative diseases and neurological disorders, because glial cells, especially astrocytes, serve as key elements in the formation, maintenance, and refinement of synapses [13][14][15]. In our earlier studies regarding the neuroprotective ability of AUR, we revealed that (1) AUR has the ability to suppress inflammatory responses in vivo, namely, hyperactivation of microglia/astrocytes, and over-expression of inflammatory factors by astrocytes, in some mouse models of brain disorders; thus, resulting in the suppression of neuronal death in the hippocampus [3][4][5][6]; and (2) AUR has the ability to induce GDNF expression in C6 cells [9] in vitro. This series of our studies thus suggested that the site of neuroprotective ability of AUR might be astrocytes.…”
Section: Discussionmentioning
confidence: 96%
“…The present findings suggested that some of the neuroprotective effects exerted by AUR could, in part, have resulted from enhanced synthesis/secretion of BDNF by neurons themselves. The amount of BDNF secreted by neuro2a cells was very low (a few pg/mL; Figure 3), whereas that of GDNF secreted by C6 cells was about 10 times as high (tens of pg/mL) [9], probably depending upon the difference in their mechanism of action; BDNF might be neuroprotective in an autocrine manner, and GDNF, in a paracrine one. As previous reports indicated that astrocytes [16] and C6 cells [12] were able to synthesize BDNF, we investigated whether AUR could induce BDNF expression in C6 cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations